(untitled) (Bulletin KNOB, 1992)
The notion that the Sint-Servaas church in Maastricht served as a burial chapel for the two last Carolingians in the male line, which idea is to be found, for instance, in the article by T.A.S.M. Panhuysen in Bulletin KNOB 1991, 15-24, is disputed in this article on the strength of historical source research. As far as Duke Otto (+1005/1006) is concerned, this is based on the error that Duke Karel van Lotharingen (+993) was considered to have been the last Carolingian. There are no archaeological data or historical sources supporting the view that Duke Otto was buried in Maastricht. On the other hand, it is beyond doubt that a burial monument for Duke Karel did exist in this church. This is evident from the reproduction in 1688 of a lead tablet dating from 1001, which was found in the crypt of the Sint-Servaas church in 1666. This tablet was lost. On June 16th 1988 the tomb and memorial cross of provost Humbert, dating from 1086, were excavated, on which mention is made of a ’sepulchrum’ of Duke Karel. Since the text on the lead tablet dating from 1001 is hardly to be interpreted otherwise than as a reference to a cenotaph, and since the historical data make a burial of Duke Karel in Maastricht anything but likely, the interpretation of ’sepulchrum’ as a ’memorial stone’ is obvious.